Validation of an Instrument for Assessing Elder Care Needs in Iran - Rashidi K (Dove Medical Press, 2020)
Kavoos Rashidi,1 Amir Jalali,2 Nader Salari,3 Parvin Abbasi4 1Department of Psychiatric Nursing, Student Research Committee, Kermanshah University of Medical Sciences, Kermanshah, Iran; 2Substance Abuse Prevention Research Center, Research Institute for Health, Kermanshah University of Medical Sciences, Kermanshah, Iran; 3Department of Biostatistics Department, School of Nursing & Midwifery, Kermanshah University of Medical Sciences, Kermanshah, Iran; 4Department of Nursing, School of Nursing and Midwifery, Kermanshah University of Medical Sciences, Kermanshah, IranCorrespondence: Amir JalaliSubstance Abuse Prevention Research Center, Research Institute for Health, Kermanshah University of Medical Sciences, Kermanshah, IranEmail jalali_amir@yahoo.comBackground: The notable growth of the senior citizens population has caused problems and concerns in areas like healthcare, social care, and participation in society. The present paper is aimed at validating a Farsi version of the “International classification of functioning, disability, and health” for assessing elderly care needs in Kermanshah, Iran.Methods: The original version of the tool was translated into Farsi using forward-backward method. The study group consisted of 301 senior citizens who were selected through cluster sampling. Validity of the tool was examined using Waltz and Basel’s content validity index, face validity, and confirmatory factor analysis. The reliability of the tool was examined using Cronbach’s alpha and internal correlation. Data analyses were performed in SPSS-25 and Amoss-16.Results: Following confirmatory factor analysis, the number of factors decreased from nine to eight. The R2 index in the above model was estimated equal to 0.99; this indicates that 99% of the dependent variable changes (total score of ICF) are explained by the independent variables (eight items). All the indices were above 0.9, which indicates significance of the model (χ2/DF=2.7, CFI, NFI, GFI, TLI=0.9, REMSEA=0.078, R2=0.99). In addition, using internal correlation, the reliability of the tool obtained was equal to 0.77 for the whole tool and 0.7– 0.87 for the sub-scales.Conclusion: The Farsi version of ICF had acceptable and applied specifications to assess the care needs of senior citizens and it can be used as a valid tool in different areas of nursing performance and elderly health.Keywords: validity, reliability, psychometric, elder care needs, Iranian population